Grundtvigs betydning for samfundet - Fabricius Møller, Jes (Grundtvig-Studier, 2015)
Grundtvig’s Impact on Society This article revisits the assumption commonly made in literature about the significance of N.F.S. Grundtvig to Danish society, that his importance hardly can be overrated. In a re-evaluation of his influence 1) on the Danish welfare state, 2) on the first folk high schools, and 3) on the Danish constitution of 1849, the study comes to the following mainly negative conclusions: 1) While he is credited for intitiating the Danish welfare state model, in fact, he did not want poor relief to be financed by a general tax. Grundtvig is often quoted as saying that there are “a few having too much, and fewer too little.” This statement is often misinterpreted to mean that Grundtvig desired a matrix for general state driven egalitarian redistribution of funds. The opposite is true. 2) While he is called the creator of the folk high school, the fact is that the first advanced school for peasants in the Oldenburg Monarchy was erected in Rendsburg in 1842. It sparked the initiative to establish a similar school for Danes in Rødding (established 1844), which was only indirectly inspired by Grundtvig. In 1856 a public donation celebrating his 70th birthday three years earlier enabled Grundtvig to open a folk high school in his own name. However, he did not have much to do with it. The ties between the folk high school movement and Grundtvig did not grow stronger until the 1860’s. 3) And finally, regarding Grundtvig’s role in the creation of the 1849 constitution, Grundtvig favoured freedom of speech and belief. It has been argued that liberalism in general and John Locke in particular inspired him. And Grundtvig has been canonized as one of the fathers of Danish democracy and as a champion of freedom in general. In fact, however, he spoke out in favour of absolutism as late as 1850. If Grundtvig is to be interpreted as a contender of natural law, the possible inspiration from Thomas Hobbes must be taken into consideration. Having undeniably strong traits of liberalism in his political portfolio, the elements of conservatism cannot be ignored